URGENSI KETELADANAN DALAM PENDIDIKAN ISLAM - Sriyatun (LP3M STIT Al Urwatul Wutsqo Jombang, 2021)
Teachers are professional educators with the main task of educating, teaching, guiding, directing, training, assessing, and evaluating students in early childhood education, formal education, primary education, and secondary education. The educational process means that every educator must try to be a role model for his students. Example in all goodness and not vice versa. Teachers must be able to set an example, be gentle and teach good manners, always try to maintain good morals and also to give testaments about various knowledge and rules of shari'ah. So important is an example in the effort to form a child's personality, so that to achieve its success, Islamic education tries to apply the exemplary method in its education system. However, the problem that exists is from the educator factor, including the teacher. Today's teachers are lacking and don't even pay attention to exemplary aspects in the educational process.